2022
DOI: 10.1111/1759-7714.14453
|View full text |Cite
|
Sign up to set email alerts
|

ACT001 inhibits the proliferation of non‐small cell lung cancer cells by upregulating NKTR expression

Abstract: Background Lung cancer, the primary cause of cancer‐related deaths worldwide, is diagnosed at an advanced stage and has a poor prognosis. Non‐small cell lung cancer (NSCLC) is a major histological type of lung malignancy. This study investigated the effect of ACT001, a novel sesquiterpene lactone derivative, on the proliferation of NSCLC cells and explored the underlying mechanism. Methods The effect of ACT001 on cell proliferation was examined by clone formation and MTT assay. Differentially expressed genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Consistent with this obsergation, we found that ACT001 could also inhibit cell proliferation, migration, and invasiveness, while promote cell apoptosis in NSCLC. Besides, we veri ed the effect of ACT001 on cell cycle progression in NSCLC cells, and found ACT001 induce G1/S arrest which were similar to the results of Dingzhi Huang et al [19] .These results add new evidence supporting the anti-tumor effects of ACT001 in NSCLC.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with this obsergation, we found that ACT001 could also inhibit cell proliferation, migration, and invasiveness, while promote cell apoptosis in NSCLC. Besides, we veri ed the effect of ACT001 on cell cycle progression in NSCLC cells, and found ACT001 induce G1/S arrest which were similar to the results of Dingzhi Huang et al [19] .These results add new evidence supporting the anti-tumor effects of ACT001 in NSCLC.…”
Section: Discussionsupporting
confidence: 85%
“…While accumulating evidence attests to the anti-tumor effects of ACT001 across various cancer types, research speci cally targeting non-small cell lung cancer (NSCLC) remains limited. Recently, Dingzhi Huang et al demonstrated that ACT001 inhibited NSCLC cell proliferation by upregulating NKTR expression [19] . However, the anti-tumor effects of ACT001 and its underlying mechanisms remain poorly understood in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has even been shown that ACT001 inhibits the G1/S transition in NSCLC cell lines. [25] Then in validating proteins in the apoptotic and proliferative pathways of myeloma cells, we found that in addition to the phosphorylated proteins, total STAT3 and NF-KB were also almost decreasing with increasing drug concentration. This appears to be a small divergence from the results of the existing studies.…”
Section: Discussionmentioning
confidence: 88%
“…[24] The antitumor effects of ACT001 have also been reported in non-small cell lung cancer, human breast cancer, and pancreatic ductal adenocarcinoma. [25,26,27] From the analysis of existing studies, in addition to anti-tumor effects, it is speculated that ACT001 a multi-targeted small molecule immune-inflammatory modulator.ACT001 inhibits nuclear translocation of NFκB in microglia by inhibiting AKT phosphorylation, which reduces the activation of the NLRP3 inflammasome, and ultimately down-regulates the neuroinflammatory response in microglia. [28]Similar results were confirmed in radiation-induced lung injury (RILI), [29]and even ACT001 alleviated NLRP3-mediated neuroinflammation in Parkinson's disease mice.…”
Section: Introductionmentioning
confidence: 99%